COVID-19 in pregnancy by race and ethnicity: Implications for development of a vaccination strategy. (December 2021) - Pressman, Alice; Lockhart, Stephen H; Wilcox, Joseph; Smits, Kelly; Etzell, Joan; Albeiroti, Sami; DeRee, Michele; Flaherty, Christine; Genolaga, Sheila; Goodreau, Michelle; Refai, Farah; Restall, Alexandra; et al.
Objective: COVID-19 and associated morbidity and mortality has disproportionately affected minoritized populations. The epidemiology of spread of COVID-19 among pregnant women by race/ethnicity is not well described. Using data from a large healthcare system in California, we estimated prevalence and spread during pregnancy and recommend a vaccination approach based on minimizing adverse outcomes. Methods: Patients delivering at Sutter Health are tested (molecular) for COVID-19. These results were combined with antibody test results, using samples drawn at delivery. For each racial/ethnic group, we estimated prevalence of COVID-19, using logistic regression to adjust for known sociodemographic and comorbid risk factors. Testing for immunoglobulin G and immunoglobulin M provided insight into timing of infections. Results: Among 17, 446 women delivering May–December, 460 (2.6%) tested positive (molecular). Hispanic women were at 2.6 times the odds of being actively infected as White women (odds ratio = 2.6, 95% confidence interval = 2.0–3.3). August and December were the highest risk periods for active infection (odds ratio = 3.5, 95% confidence interval = 2.1–5.7 and odds ratio = 6.1, 95% confidence interval = 3.8–9.9, compared with May, respectively). Among 4500 women delivering October–December, 425 (9.4%) had positive molecular or antibody tests, ranging from 4.0% (Asian) to 15.7% (Hispanic). Adjusting for covariables, compared with White patients, odds of infection was similar for Black and Asian patients, with Hispanic at 2.4 (1.8–3.3) times the odds. Conclusion: COVID-19 prevalence was higher among Hispanic women at delivery and in the last trimester than their White counterparts. Higher rates in Black patients are explained by other risk factors. Resources should be directed to increase vaccination rates among Hispanic women in early stages of pregnancy.